Nobinobi Yomikaki: Teaching Materials for Japanese Reading and Writing Based on 21st Century Skills - Frida Philiyanti; Cut Erra Rismorlita (Universitas Muhammadiyah Yogyakarta, 2023)
This study aims to determine the use of